2017
DOI: 10.3390/catal7120360
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Magnetic Photocatalysts for Water Treatment. The Effect of Particle Charge on Surface Functionality

Abstract: Core-interlayer-shell Fe 3 O 4 /SiO 2 /TiO 2 , CoFe 2 O 4 /SiO 2 /TiO 2 and BaFe 12 O 19 /SiO 2 /TiO 2 magnetic photocatalysts were obtained. A water-in-oil microemulsion system with suitable surfactants was used for functionalization of the magnetic core with silica interlayer and TiO 2 -based photocatalyst. Uncoated and coated particles were characterized by electrophoretic measurements, X-ray diffractometry (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), specific surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…Samples possess spherical together with hexagonal shaped grains. Similar morphology was observed for Barium hexaferrite with diameter 50-70 nm by Jurek et al[41]. Also, it is noticed that the…”
supporting
confidence: 85%
“…Samples possess spherical together with hexagonal shaped grains. Similar morphology was observed for Barium hexaferrite with diameter 50-70 nm by Jurek et al[41]. Also, it is noticed that the…”
supporting
confidence: 85%
“…Therefore, a mechanically stable core has been proposed, such as magnetic Fe 3 O 4 , which additionally allows the fast and easy separation of photocatalysts after reactions in the magnetic field [109][110][111]. However, the photoreaction between a core and a shell might result in the instability of the photocatalyst (e.g., dissolution of iron), and thus an insulator interlayer has been applied by Zielinska-Jurek et al between a magnetic core and titania shell, as shown in Figure 6 [110].…”
Section: Core-shell Titania Compositesmentioning
confidence: 99%
“…Core-interlayer-shell NPs composed of Fe3O4 (core), SiO2 (interlayer), and TiO2 (shell): (a) Nanostructure scheme; and (b) Mapping of Fe3O4, SiO2, and TiO2 in Fe3O4/SiO2/TiO2) photocatalyst prepared by the microemulsion method (Fe-red, Si-green, and Ti-blue); adapted from[110]. Copyright 2017 Creative Commons Attribution.…”
mentioning
confidence: 99%
“…In this regard, the introduction of a silica intermediate passive layer could prevent an injection of charge carriers from titania shell into the iron oxide core and the subsequent leaching of iron ions into the solution [ 5 ]. The functionalization of the magnetic core consisting of magnetite [ 6 ], maghemite [ 7 ], hematite [ 8 ], CoFe 2 O 4 [ 9 ], ZnFe 2 O 4 spinel ferrites [ 10 ], BaFe 12 O 19 hexagonal ferrites [ 9 ], bimetallic nanoparticles of Fe-Ni, Co-Fe, Mn-Zn, Ni-Cu-Zn [ 11 , 12 ] with TiO 2 and intermediate SiO 2 passive layer has recently been investigated.…”
Section: Introductionmentioning
confidence: 99%